The meaning of modern business : an introduction to the philosophy of large corporate enterprise - Eells, Richard Sedric Fox (New York : Columbia University Press, 1960)
This book has been written as an introduction to the philosophy of a great institution-the modern business corporation. Such a philosophy, when finally matured, will make the corporation more comprehensible and provide norms for corporate performance in a society that relies so heavily upon this remarkable organizational instrument.
Includes bibliographical references and index.
hza 24/08/2018
Loans
Keywords: Corporations